Effectiveness of "Buku Pintar" in Solving Student's Procrastination to Thesis - Nur, Haerani (Indonesian Journal of Educational Studies, 2013)
This study used an experimental method that aims to determine the effectiveness of â€œbuku pintar penulisan skripsiâ€ in overcoming barriers to students so as to reduce student procrastination to the thesis. Respondents in this study were two students of the Faculty of Psychology UNM. The results of this study indicate that, â€œbuku pintar penulisan skripsiâ€ could reduce student procrastination in all aspects of the thesis, although not all aspects of a significant decline. Factors that cause changes to the thesis procrastination is not significant in every aspect is the thesis supervisor, and addicted to playing games on the students.